Synthesis of poly(1‐chloro‐2‐arylacetylene)s with high cis‐content and examination of their absorption/emission properties. Issue 3 (2nd November 2016) - Rodriguez Castanon, Jesus; Sano, Natsuhiro; Shiotsuki, Masashi; Sanda, Fumio
ABSTRACT: A series of 1‐chloro‐2‐arylacetylenes [Cl‐CC‐Ar, Ar = C6 H5 (1 ), C6 H4 ‐ p ‐ i Pr (2 ), C6 H4 ‐ p ‐O i Pr (3 ), C6 H4 ‐ p ‐NHC(O)O t Bu (4 ), and C6 H4 ‐ o ‐ i Pr (5 )] were polymerized using (tBu3 P)PdMeCl/silver trifluoromethanesulfonate (AgOTf) and MoCl5 /SnBu4 catalysts. The corresponding polymers [poly(1 )–poly(5 )] with weight‐average molecular weights of 6, 500–690, 000 were obtained in 10–91% yields. THF‐insoluble parts, presumably high‐molecular weight polymers, were formed together with THF‐soluble polymers by the Pd‐catalyzed polymerization. The Pd catalyst polymerized nonpolar monomers1 and2 to give the polymers in yields lower than the Mo catalyst, while the Pd catalyst polymerized polar monomers3 and4 to give the corresponding polymers in higher yields. The 1 H NMR and UV–vis absorption spectra of the polymers indicated that the cis‐contents of the Pd‐based polymers were higher than those of the Mo‐based polymers, and the conjugation length of the Pd‐based polymers was shorter than that of the Mo‐based polymers. Pd‐based poly(5 ) emitted fluorescence most strongly among poly(1 )–poly(5 ). © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 382–388 Abstract : A series of 1‐chloro‐2‐arylacetylenes1 –5 were polymerized using ( t Bu3 P)PdMeCl/silver trifluoromethanesulfonate (AgOTf) and MoCl5 /SnBu4 catalysts. The 1 H NMR and UV–vis absorption spectra of the polymers indicated that the cis‐contents of the Pd‐based polymers were higher than those of the Mo‐based polymers, and the conjugation length of the Pd‐based polymers was shorter than that of the Mo‐based polymers. Pd‐based poly(5 ) emitted fluorescence most strongly among poly(1 )–poly(5 ).